Paperback Oxford Large Print Thesaurus (Oxford University Press, 2004)
Authoritative, up-to-date, and with exceptionally clear print, the Paperback Oxford Large Print Thesaurus contains over 130,000 alternative and opposite words, drawing on the most recent findings of the language research programme at Oxford University Press. Its clear page layout, designed in association with the Royal National Institute for the Blind, offers enlarged fonts, larger margins, generous line-spacing, and good quality paper, making it quick and easy to find the word you need. Special attention has been given to the binding and choice of paper, ensuring that there is minimum 'glare' and 'show-through'. Ideal for both adults and children, particularly those with vision impairment, the Paperback Oxford Large Print Thesaurus is a valuable reference tool for use at home, school, or the office, and is great for word games. Lightweight and affordable, it is also the perfect companion to the Paperback Oxford Large Print Dictionary